Design of a Cascaded DC High Voltage Generator Based on Cockcroft-Walton Voltage Doubler Circuit - Bhattacharya, Shuva; Mazumder, Debkumar; Bose, Taina; Kumar Das, Malay; Ghosal, Suman; Jana, Sougata (International Journal of Computer Sciences and Engineering, 2025)
This paper presents a high step-up dc-dc converter based on the Cockcroft-Walton (CW) voltage multiplier without using step-up transformer. The proposed converter is quite suitable for applying low-input dc voltage, to high output dc voltage generation systems. It provides continuous input current to load with low ripple voltage and current. Voltage stress on the all switching device, diodes, and capacitors can be minimised. Moreover, based on the 2-stage Cockcroft-Walton (CW) voltage multiplier, the proposed converter can provide a suitable dc source like solar cells, fuel cell and other type source cascaded for HV generation. In this paper, the control strategy employs two independent frequencies, one operates at high frequency to minimize the size of the inductor and other one operates at relatively low frequency to the desired output voltage ripple. The simulations carried over by the MATLAB-Simulink and Proteus Simulator.